2018
DOI: 10.1007/s10933-018-0028-x
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution pigment and productivity record from the varved Ponte Tresa basin (Lake Lugano, Switzerland) since 1919: insight from an approach that combines hyperspectral imaging and high-performance liquid chromatography

Abstract: A high-resolution pigment and productivity record from the varved Ponte Tresa basin (Lake Lugano, Switzerland) since 1919: insight from an approach that combines hyperspectral imaging and high-performance liquid chromatography A high-resolution pigment and productivity record from the varved Ponte Tresa basin (Lake Lugano, Switzerland) since 1919: insight from an approach that combines hyperspectral imaging and high-performance liquid chromatography Abstract Eutrophication, prompted by anthropogenic activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…The significant eutrophication in Lake Burgä schi might have caused intensified CaCO3 precipitation and sulfur (S) deposition to sediments (Fig. 4 and 5), which is in agreement with the findings from many other eutrophic lakes (Bonk et al, 2016;Holmer and Storkholm, 2001;Schneider et al, 2018).…”
Section: Trophic State Evolution Of Lake Burgä Schisupporting
confidence: 90%
See 2 more Smart Citations
“…The significant eutrophication in Lake Burgä schi might have caused intensified CaCO3 precipitation and sulfur (S) deposition to sediments (Fig. 4 and 5), which is in agreement with the findings from many other eutrophic lakes (Bonk et al, 2016;Holmer and Storkholm, 2001;Schneider et al, 2018).…”
Section: Trophic State Evolution Of Lake Burgä Schisupporting
confidence: 90%
“…RABD590-765. Butz et al (2017) and Schneider et al (2018) revealed that this index is well calibrated to absolute green-pigments concentrations (chlorophyll a + pheophytin a) in sediments.…”
Section: Non-destructive Geochemical Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, few studies focused on long-term changes in the entire phytoplankton community have been considered in Chilean coastal lakes to explain their response to environmental conditions [6,9,[28][29][30]. Sedimentological and biological proxies such as (sub)fossil remains, total organic carbon concentration, C and N stable isotopes and phytoplankton pigments can provide valuable information on past changes in primary production and the phytoplankton community structure [6,7,[31][32][33][34][35][36][37][38][39]. Phytoplankton pigments have the advantages that they also allow for the study of soft-bodied organisms which do not readily fossilise.…”
Section: Introductionmentioning
confidence: 99%
“…HSI can improve chemical knowledge by analyzing the sample surface. It has already been used to characterize mineralogical fingerprints (Feng et al, 2018;Lorenz et al, 2019;Tusa et al, 2020), organic matter (Jacq et al, 2019b;Van Exem et al, 2019), pigments (Butz et al, 2017;Makri et al, 2020;Schneider et al, 2018), and particle size distribution (Jacq et al, 2019a). Some of these studies highlight sedimentary structures with proxy's estimation but without characterizing them spatially.…”
Section: Introductionmentioning
confidence: 99%